2010
DOI: 10.1159/000298751
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine-Arabinoside-Induced Keratopathy: A Model of Corneal Proliferation Kinetics

Abstract: Aims: The use of the chemotherapeutic cytosine arabinoside (Ara-C) causes an ocular toxic reaction, characterized by aspecific keratopathy. We examined the pathway of the damaged cells by in vivo confocal microscopy. Methods: Prospective study of 11 patients with acute myeloic leukemia treated with high-dose Ara-C. Ten eyes developed fluorescein-negative punctate keratopathy, and were examined by slit lamp and in vivo confocal biomicroscopy at days 1, 3–4 and 9–14 after the beginning of ocular symptoms. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…Diffuse "mild to moderate punctate keratopathy," with "intraepithelial opacities" most "numerous in central cornea" 28 Yes, it resolves in 14 days without cessation of the drug 28 Photophobia, foreign body sensation, pain, 28 Conjunctivitis, cataract 18 EGFR, epidermal growth factor receptor; HER2, human epidermal growth factor receptor 2; NSAID, nonsteroidal anti-inflammatory drug; NSCLC, nonesmall-cell lung cancer; VEGFR2, vascular endothelial growth factor receptor 2. chloroquine use can result in irreversible retinopathy, which can progress even after the drug is discontinued. 11 The presence of a marked vortex pattern of corneal deposits is associated with advanced retinopathy, with 50% sensitivity and 90% specificity.…”
Section: Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Diffuse "mild to moderate punctate keratopathy," with "intraepithelial opacities" most "numerous in central cornea" 28 Yes, it resolves in 14 days without cessation of the drug 28 Photophobia, foreign body sensation, pain, 28 Conjunctivitis, cataract 18 EGFR, epidermal growth factor receptor; HER2, human epidermal growth factor receptor 2; NSAID, nonsteroidal anti-inflammatory drug; NSCLC, nonesmall-cell lung cancer; VEGFR2, vascular endothelial growth factor receptor 2. chloroquine use can result in irreversible retinopathy, which can progress even after the drug is discontinued. 11 The presence of a marked vortex pattern of corneal deposits is associated with advanced retinopathy, with 50% sensitivity and 90% specificity.…”
Section: Nomentioning
confidence: 99%
“…83 At least 80% of patients treated with ara-C at high doses (>1 g/m 2 ) can have symptoms of photophobia, foreign body sensation, and pain and can present with diffuse punctate keratopathy, with numerous intraepithelial opacities in the central cornea, but visual acuity is unaffected. 28 The symptoms and deposits resolve without cessation of the drug in approximately 2 weeks. 28 Lochhead and colleagues reported a few cases of toxicities at lower doses, 1 of which was a patient with epithelial microcysts in the central cornea that were accompanied by blurred vision, severe discomfort, photophobia, severe blepharospasm, and moderate conjunctival inflammation.…”
Section: Antineoplastic Agents (Noncationic/amphiphilic)mentioning
confidence: 99%
See 1 more Smart Citation
“…This corneal toxicity is reversible when therapy is discontinued; the corneal epithelium returns to normal usually within 2 weeks, with no reported permanent damage or scarring 2 3. It has been shown that the use of prophylactic topical corticosteroids is effective in preventing ocular toxicity in high-dose Ara-C therapy 7.…”
Section: Discussionmentioning
confidence: 99%
“…This type of punctate keratopathy with fine bilateral fluorescein-negative epithelial opacities is reported to be a frequent finding in patients receiving high-dose Ara-C 1. On in vivo confocal microscopy they are not seen as cystic spaces but instead as highly reflective, disseminated, granular, irregular intraepithelial opacities measuring 10–15 µm in diameter 2. Essentially, the microcysts as seen on slit-lamp biomicroscopy appear as hyper-reflective opacities on IVCM.…”
Section: Answers (For Questions See 138)mentioning
confidence: 95%